Screening of Eating Disorders Risk with Scoff Tool on Adolescents in Samarinda City - Sitti Badrah; Reny Noviasty; Rahmi Susanti (Journal La Medihealtico, 2020)
Adolescents’s Eating behavior that generally expects slim body increases the risk of eating disorders which causes poor nutritional needs. The objective was to identify the risk of eating disorder with SCOFF Tools for students in SMAN/S in Samarinda. The design was quantitative descriptive with SCOFF Screening instrument consisting 5 questions namely makin yourself (sick); Worry having lost (Control); Lost more than 6,35kg (One Stone); Believing Yourself (Fat); (Food) dominated your life. The random sampling technique use to selection that located in Samarinda consisting of 10 districts with a total of 39 SMAN/S high schools by measuring changes in eating disorders. The analysis using Pearson correlation test and simple linear regression. The research was obtained by 812 respondents from 19 SMAN/S in Samarinda. The data collection based on age there are 273 students aged 16 years, 25 students aged 14 years and 82 students aged over 17. There are 468 students who have a normal BMI, 35 students are mildly obese and 60 students are mild having overweight status and BMI under 17 as many as 124 students who are underweight. Eating disorder risk screening results with the SCOFF Tool found 57.4% of high school children are at risk of eating disorders. It can be concluded that adolescents in Samarinda tend to be at risk of eating disorders so that early intervention is needed to prevent prolonged malnutrition.